2016
DOI: 10.1016/j.canlet.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Developing oxygen-enhanced magnetic resonance imaging as a prognostic biomarker of radiation response

Abstract: Oxygen-Enhanced Magnetic Resonance Imaging (OE-MRI) techniques were evaluated as potential non-invasive predictive biomarkers of radiation response. Semi quantitative blood-oxygen level dependent (BOLD) and tissue oxygen level dependent (TOLD) contrast, and quantitative responses of relaxation rates (ΔR1 and ΔR2*) to an oxygen breathing challenge during hypofractionated radiotherapy were applied. OE-MRI was performed on subcutaneous Dunning R3327-AT1 rat prostate tumors (n = 25) at 4.7 T prior to each irradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 58 publications
2
60
2
Order By: Relevance
“…Tissues were placed in liquid nitrogen and formalin. Slides for hematoxylin and eosin (H&E) were fixed in 4% paraformaldehyde, rinsed, and then subjected to a progressive staining line containing Leica SelecTech reagents (Hematoxylin 560 and Alcoholic Eosin‐Y 515; Leica Biosystems, Wetzlar, Germany) according to well‐established standard protocols . At the time of imaging, multiple 1600 × 1200 pixel subfields were acquired to cover the entire tumor and surrounding tissue at 10× objective magnification on a Nikon E600 compound photomicroscope (Nikon USA, Melville, NY) equipped with epifluorescence and bright‐field illumination, an Applied Scientific Instruments x‐y‐z motorized stage (Applied Scientific Instruments, Eugene, OR), and a Nikon DS‐Fi2 CCD camera.…”
Section: Methodsmentioning
confidence: 99%
“…Tissues were placed in liquid nitrogen and formalin. Slides for hematoxylin and eosin (H&E) were fixed in 4% paraformaldehyde, rinsed, and then subjected to a progressive staining line containing Leica SelecTech reagents (Hematoxylin 560 and Alcoholic Eosin‐Y 515; Leica Biosystems, Wetzlar, Germany) according to well‐established standard protocols . At the time of imaging, multiple 1600 × 1200 pixel subfields were acquired to cover the entire tumor and surrounding tissue at 10× objective magnification on a Nikon E600 compound photomicroscope (Nikon USA, Melville, NY) equipped with epifluorescence and bright‐field illumination, an Applied Scientific Instruments x‐y‐z motorized stage (Applied Scientific Instruments, Eugene, OR), and a Nikon DS‐Fi2 CCD camera.…”
Section: Methodsmentioning
confidence: 99%
“…Prostate tumors that are well reoxygenated during pure oxygen breathing before radiotherapy display a significantly larger regrowth delay than low responders to hyperoxia (92). Combined BOLD and TOLD contrasts were also recently assessed in Dunning rat prostate tumors and were shown to be useful prognostic factors for predicting tumor response to hypofractionation (121). However, these results remain preliminary and need to be further investigated.…”
Section: Mri Methodsmentioning
confidence: 99%
“…Linnik et al reported excellent correlation between percentage of “negative AUC OE ” ( O 2 ‐negative) voxels and percentage of hypoxic areas in the highly vascular preclinical U87MG tumor xenografts . A second approach for differentiating between viable but hypoxic regions and unperfused dead tissues, is to combine OE‐MRI with T2* W acquisition and the BOLD effect to classify regions that show both effects. Excess oxygen in the blood will induce changes in Hb saturation, which alter the T2* resulting in a robust measure of areas with functioning vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…To help understand the oxygen dynamics in tumors, including the effect of hemoglobin with T2* mapping, fitting exponential recovery and decay curves to the extracted oxygen response curves may provide additional insights as originally proposed by Losert et al in the brain . In a promising study, White et al has shown that OE‐MRI may be very relevant in developing prognostic factors to predict tumor response to hypofractionation by stratifying tumors that may benefit from oxygen breathing during irradiation . Featherstone et al have recently explored pre‐clinical datasets using feature‐extraction and clustering analysis and this may prove fruitful in understanding the behavior of subregions within a tumor microenvironment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation